Market Transparency, Adverse Selection, and Moral Hazard - Tobias J. Klein; Christian Lambertz; Konrad O. Stahl (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We study the effects of improvements in market transparency on eBay on seller exit and continuing sellers' behavior. An improvement in market transparency by reducing strategic bias in buyer ratings led to a significant increase in buyer valuation especially of sellers rated poorly prior to the change, but not to an increase in seller exit. When sellers had the choice between exiting'a reduction in adverse selection'and improved behavior'a reduction in moral hazard', they preferred the latter because of lower cost. Increasing market transparency improves on market outcomes.
urn:nbn:de:bvb:19-epub-17291-0
Keywords: D47; D83; L15; 330; Anonymous markets; adverse selection; moral hazard; reputation building mechanisms; market transparency; market design